Corporate governance characteristics and financial performance: evidence from Islamic banks in Malaysia / Mohd Danial Afiq Khamar Tazilah ... [et al.] - Khamar Tazilah, Mohd Danial Afiq; Majid, Muhammad; Aweea, Azeyan; Aik Keang, Adam Arif Lee (Universiti Teknologi MARA, 2021)
Corporate governance has been proven to be an effective mechanism in managing business operations that have major impact on the financial performance, increase investor confidence level and goodwill. Past studies have focused more towards the relationship between corporate governance and financial performance among various industries including financial services. However, limited studies explored in overseeing the performance of Islamic financial services in relation to the implementation of Shariah governance principles since 2010 which are fully governed by the Central Bank of Malaysia. Hence, this research aimed to investigate the relationship between corporate and Shariah governance characteristics (board size, board independence, CEO duality, size of the Shariah Committee and disclosure of the Sharia Committee Report) and bank performance (return on equity) among Islamic banks in Malaysia. A total of 16 Islamic banks listed in Bursa Malaysia were selected and data from the annual reports were collected and analysed from 2011 to 2018. This research shall provide greater insights to various stakeholders and shareholders as the potential investors. It gives better and clear understanding of the functions of both corporate and Shariah governance in enhancing the performance and operation activities of Islamic banks in Malaysia